Recent Developments in Isothermal Amplification Methods for the Detection of Foodborne Viruses - Suther, Cassandra; Stoufer, Sloane; Zhou, Yanjiao; Moore, Matthew D. (Frontiers in Microbiology, 2022)
Foodborne and enteric viruses continue to impose a significant public health and economic burden globally. As many of these viruses are highly transmissible, the ability to detect them portably, sensitively, and rapidly is critical to reduce their spread. Although still considered a gold standard for detection of these viruses, real time polymerase chain reaction (PCR)-based technologies have limitations such as limited portability, need for extensive sample processing/extraction, and long time to result. In particular, the limitations related to the susceptibility of real time PCR methods to potential inhibitory substances present in food and environmental samples is a continuing challenge, as the need for extensive nucleic acid purification prior to their use compromises the portability and rapidity of such methods. Isothermal amplification methods have been the subject of much investigation for these viruses, as these techniques have been found to be comparable to or better than established PCR-based methods in portability, sensitivity, specificity, rapidity, and simplicity of sample processing. The purpose of this review is to survey and compare reports of these isothermal amplification methods developed for foodborne and enteric viruses, with a special focus on the performance of these methods in the presence of complex matrices.